Tratamento ácido na fermentação etanólica: efeito sobre a viabilidade e vitalidade de linhagens industriais de Saccharomyces cerevisiae - Jesus, Gabriel Scanavachi de (Universidade Federal de São Carlos, 2025)
The control of contaminant microorganisms in Brazilian sugar-ethanol industries frequently involves the use of sulfuric acid, which, when applied at the end of each fermentation cycle, not only controls contaminant bacteria but also promotes deflocculation of the yeast, contributing to ethanol production efficiency. Few studies have investigated the effect of acid treatment on the yeasts responsible for the fermentative process, particularly regarding viability — understood as the proportion of living cells capable of reproduction — and vitality — defined as the functional and physiological capacity of cells to carry out metabolic activities. In this study, we evaluated the effect of sulfuric acid treatment (pH 2.5; 2 h) on the viability and vitality of Saccharomyces cerevisiae cells, using the industrial strains PE-2 and CAT-1 in fed-batch fermentation with cell recycling, in sugarcane broth, over six fermentation cycles. We analyzed CFU/mL, number of viable cells/mL (erythrosine staining), viability (%), budding (%), growth in liquid medium and counting of bud scars, as well as alcohol content (g/100 mL), final pH, residual total reducing sugars (g/100 mL) and yield (g ethanol/g total reducing sugars) after each cycle of cell treatment. A control fermentation without acid treatment was also conducted, using water in place of the acid. In the PE-2 strain, acid treatment significantly affected viability (%), budding (%), specific growth rate (μmax, h⁻¹) and change in absorbance. However, fermentative yield was not compromised by the acid treatment, suggesting an adaptive profile capable of sustaining fermentative capacity; in contrast, the CAT-1 strain showed greater sensitivity to acid stress, with effects on budding (%), alcohol content (g/100 mL) and sugar consumption (g/100 mL). The increase in budding occurred concomitantly with accumulation of residual sugars and reduction in yield, indicating a prioritization of survival and cell division at the expense of fermentative efficiency. Moreover, analysis of bud scars revealed evidence of selection for metabolically active cells accompanied by death of young cells, a behavior that did not vary markedly between strains or treatments. Taken together, these results indicate that, although the CAT-1 strain persists across cycles, it exhibits a lower fermentative yield than PE-2 in the presence of acid treatment, probably due to lower tolerance to the acid treatment and a stronger mobilization of growth strategies to maintain cell viability during fermentation.
Acid treatment in ethanol fermentation: effect on the viability and vitality of industrial strains of Saccharomyces cerevisiae
Keywords: Biocombustível; Fermentação em batelada; Vitalidade; Viabilidade; Biofuel; Batch fermentation; Vitality; Viability; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO; 7. Energia limpa e acessível